A Preparatory Study for a Randomized Controlled Trial of Dietary Fiber Intake During Adult Pelvic Radiotherapy - Ahlin, Rebecca; Bergmark, Karin; Bull, Cecilia; Devarakonda, Sravani; Landberg, Rikard; Sigvardsson, Ida; Sjöberg, Fei; Skokic, Viktor; Steineck, Gunnar; Hedelin, Maria (Frontiers in Nutrition, 2021)
Background: Patients undergoing pelvic radiotherapy are often advised to omit fiber-rich foods from their diet to reduce the adverse effects of treatment. Scientific evidence supporting this recommendation is lacking, and recent studies on animals and humans have suggested that there is a beneficial effect of dietary fiber for the alleviation of symptoms. Randomized controlled studies on dietary fiber intake during pelvic radiotherapy of sufficient size and duration are needed. As preparation for such a large-scale study, we evaluated the feasibility, compliance, participation rate, and logistics and report our findings here in this preparatory study. Method: In this preparatory study of a fiber intervention trial, Swedish gynecological cancer patients scheduled for radiotherapy were recruited between January 2019 and August 2020. During the intervention, the participants filled out questionnaires and used an application. They also consumed a fiber supplement at first in powder form, later in capsules. Blood- and fecal samples were collected. The study is registered in clinicaltrials.gov (https://clinicaltrials.gov/ct2/show/NCT04534075?cond=fidura&draw=2&rank=1). Results: Among 136 approached patients, 57 started the study and the participation rate in reporting primary outcomes was 63% (third blood sample) and 65% (third questionnaire). Barely half of the participants provided fecal samples. Providing concise and relevant information to the patients at the right time was crucial in getting them to participate and stay in the study. The most common reasons for declining participation or dropping out were the expected burden of radiotherapy or acute side effects. Tailoring the ambition level to each patient concerning the collection of data beyond the primary endpoints was an important strategy to keep the dropout rate at an acceptable level. Using capsules rather than psyllium in powder form made it much easier to document intake and to create a control group. During the course of the preparatory study, we improved the logistics and for the last 12 participants included, the participation rate was 100% for the earliest primary outcome. Conclusion: A variety of adjustments in this preparatory study resulted in an improved participation rate, which allowed us to set a final protocol and proceed with the main study.